Exploring freshwater microalgae diversity in Yahuarcocha and San Pablo highland lakes for biotechnological applications in the Ecuadorian Andean - María Cevallos-Rivera; Santiago Zárate-Baca; Sania Ortega-Andrade; Gabriel Chimbo-Yépez; Diana Ramírez-Itás; Jeniffer Novoa-Rivera; Carla Sandoval-Guano (Heliyon, 2025)
Highland lakes are allocated in ecosystems with extreme weather conditions like low temperatures, high ultraviolet radiation, strong winds and low nutrient availability. Therefore, this environment exerts the expression of interesting metabolic products in microalgae cells for adaptation and survival. Most lakes in Ecuador are unexplored therefore, there is little information or research on this field. In this investigation, two important Ecuadorian Andean lakes, Yahuarcocha and San Pablo, were studied from a bioprospecting point of view. Microalgae were isolated using four culture media with varying macronutrient concentrations. The isolated microalgae were identified through morphological and molecular characterization by PCR and sequencing of the 16S, 18S and 23S rRNA gene. Cultures were incubated for 30–45 days at 26 °C with a 16:8 photoperiod cycle and a range of light intensity between 90 μmolph.m−2.d−1 to 110 μmolph.m−2.d-1. The photoperiod 24:0 was used in batch mode. From the ten identifies strains, only 7 microalgae were selected for characterization based on growth rate and biomass composition. Ettlia pseudoalveolarishas the highest growth rate, 0.92 h-1. Chloromona perforate has the highest lipid content (57 %). Protein content is ranged from 14.9 % to 61.2 % DW, and the highest protein content belongs to Pectinodemus pectinatus.